Implementation of Right of Children to Free and Compulsory Education Act (2009): A Case Study of Polba Gram Panchayat, West Bengal - Ghosh, Sohini (Journal of Ecohumanism, 2024)
The vision of the Indian New Education Policy (2020) is to provide greater access, equity, excellence, inclusion, and affordability of children to help India emerge as a knowledge superpower. In the present context, a case study has been conducted at the Polba Gram Panchayat (GP) of Hooghly District of West Bengal to study the status of implementation of the Right to Education (RTE), Act, 2009. The qualitative data are collected and analyzed from 30 villages of the said GP under 13 Mouzas having 26 habitations. According to the Census Report, 2011, the population in the Polba Panchayat is found 20,084, of which males comprise 10,150 and females 9,934. The data is collected from Panchayat office records on RTE implementation strategies and Focus Group Discussions are conducted to collect analytical data for the study. It is concluded that most of the village people are living with the hope that one day their dream of securing holistic education for all children - irrespective of their class, color, or creed - will be fulfilled. This is in fact the very essence of Article 21A of the Indian Constitution. However, there is a conclusive evidence from the study to prove that the hiatus between what is laid down by law and the ground realities is alarmingly colossal. Regarding the implementation of the RTE Act, 2009 the ideal RTE Act at the grass-root level has resulted in the path-breaking Act becoming unfortunately much less effective in some places than what it was intended to be.